Harmonizing emotions in the workplace: Exploring the interaction between emotional intelligence, positive psychological capital, and flourishing - Rodrigues, R.; Junça Silva, A. (Frontiers in Psychology, 2024)
The globalized environment has undeniably provided new opportunities for organizational growth. This expansion has brought about various changes that are reflected in the way cultural diversity is managed (Inegbedion et al., 2020). The ability to understand and manage emotions, both one's own and those of others, is essential for building effective relationships in multicultural teams (Brett et al., 2020). Therefore, the importance attributed to emotional intelligence (EI) has come to be considered the key to effective performance, as it contributes to promoting a positive work environment that is reflected in organizational performance (Blázquez Puerta et al., 2021). According to Kurdi and Hamdy (2020), this type of intelligence plays a particularly crucial role in an individual's adaptation to different spheres of life. Manifesting in situations involving the ability to perceive, express, understand, regulate, and utilize emotions to promote well-being, physical and mental health, and overall satisfaction (Brunetto et al., 2020). As a result, organizations are realizing that the technical skills of their employees are no longer sufficient for gaining a competitive advantage (Asbari et al., 2020). They highlight the need for employees to understand their own emotions and those of others to guide their thoughts, behaviors, and actions positively (Diener et al., 2020). Moroń and Biolik-Moroń (2021) add that individuals with high levels of EI are more perseverant and adopt strategies that enable them to face situations with greater confidence in the face of adversity.